KEPEMIMPINAN TRANSFORMASIONAL KEPALA SEKOLAH DALAM UPAYA PENINGKATAN MUTU PROFESIONALISME GURU - Gamaliel, Franciscus Xaverius; Widodo, Bambang Sigit (Universitas Negeri Surabaya, 2024)
This article delves into the crucial roles of school principals in fostering teacher professional development. Drawing upon a comprehensive literature review of 20 academic journals (15 international, 5 national), the study illuminates three vital facets of principal leadership: communication, counseling, and consulting. First, the research underscores the principal's role as a skilled communicator, influencing stakeholders (parents, teachers, students, staff) to align with school goals. Effective communication is identified as a cornerstone for building trust, fostering commitment, and cultivating a positive school environment. Second, the study highlights the principal's function as a counselor, providing guidance and support to teachers as they navigate their professional journey. By acting as a sounding board and offering constructive feedback, the principal empowers teachers to continually learn and refine their pedagogical practices. Finally, the research examines the principal's role as a consultant, facilitating transformative change within the teaching community. The principal serves as a catalyst for innovation, inspiring teachers to experiment with new ideas and embrace creative approaches to enhance student learning. This multifaceted approach to leadership, encompassing communication, counseling, and consulting, positions the principal as a key driver in propelling teacher professional development and ultimately optimizing educational outcomes.